2014
DOI: 10.33151/ajp.11.6.130
|View full text |Cite
|
Sign up to set email alerts
|

Pathway to Paramedicine Program Perspectives – Part 1 Paramedic Students

Abstract: IntroductionParamedic practice has evolved significantly with a greater emphasis now being placed on paramedics to perform educator type roles to junior paramedics, patients and the wider community. Paramedic training and education should therefore include preparing students for this important role. The Pathway to Paramedicine Program used a peer assisted learning (PAL) model to expose paramedic students to the educator/mentor role. The aim of this study was to evaluate the student paramedic’s perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In addition to these simulated professional interactions, Ross and Bertucci ( 2014 ) investigated student learning after being part of a peer-assisted learning (PAL) program. Paramedic students mentored high school students with an interest in a career in paramedicine and it was found that the program supported the development of interpersonal communication skills (Ross & Bertucci, 2014 ). The research unfortunately provided no more detail than that, as communication was not the primary outcome of their study.…”
Section: Presentation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these simulated professional interactions, Ross and Bertucci ( 2014 ) investigated student learning after being part of a peer-assisted learning (PAL) program. Paramedic students mentored high school students with an interest in a career in paramedicine and it was found that the program supported the development of interpersonal communication skills (Ross & Bertucci, 2014 ). The research unfortunately provided no more detail than that, as communication was not the primary outcome of their study.…”
Section: Presentation Of Resultsmentioning
confidence: 99%
“…Providing opportunities to practice interpersonal communication with patients, peers and other disciplines was a prevalent teaching method described in the literature. Practise in this manner appears to build students comfort and confidence in their interpersonal communication skills (Credland et al, 2020 ; Furseth et al, 2016 ; Johnston et al, 2014 ; Lucas et al, 2015 ; Ross & Bertucci, 2014 ; Ross & Williams, 2014 ; Stratton et al, 2015 ). Through this interaction, students are able to discover their own weaknesses and strengths in their current communication ability (Ford et al, 2014 ; Prakash et al, 2020 ; Ross & Kabidi, 2017 ; Ross et al, 2018 ) and students consider more opportunities to obtain practical experience as a way to develop their communication ability further (O’Brien et al, 2013 ; Twinley, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further details regarding the structure and content of the Pathway to Paramedicine Program can be found in the paper, Pathway to Paramedicine Program Perspectives -Part 1: Paramedic students (12). The aim of this study was to evaluate the secondary school students' perspectives on the Pathway to Paramedicine Program.…”
Section: The Pathway To Paramedicine Programmentioning
confidence: 99%
“…The article by Ross and Bertucci is the first of two articles that investigate a program for school leavers that provides information about being an undergraduate paramedic student. Part one outlines the paramedic student view of their participation in the program (2) As this is the last issue for 2014, I would like to wish the readership a happy and safe Christmas, holiday period and New Year on behalf of the editorial group and look forward to your continuing support in 2015.…”
Section: The Year That Wasmentioning
confidence: 99%
“…The article by Ross and Bertucci is the first of two articles that investigate a program for school leavers that provides information about being an undergraduate paramedic student. Part one outlines the paramedic student view of their participation in the program (2). The article by Smith looks at the effectiveness of prehospital adenosine and verapamil use in the management of supraventricular tachycardia (3).…”
mentioning
confidence: 99%